IMPLEMENTASI KEBIJAKAN KAWASAN TANPA ROKOK SEBAGAI UPAYA PEMENUHAN HAK-HAK ANAK DI KOTA SURAKART - Kinanthi Sekar Pinakesti; Augustin Rina Herawati; Teuku Afrizal (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
The Child-Friendly City Movement (KLA) was started in 2006 in Surakarta City, to realize children's rights. Child-Friendly City has 24 comprehensive indicators to measure its success, one of which is a Smoking Free Area. A smoke-free area is a place that prohibits visitors from smoking, both from producing, promoting, and marketing tobacco products. Researchers analyzed the implementation of the No-Smoking Area policy in Surakarta using the Cluster of Children's Rights and Van Meter and Van Horn's theory (1975). This study used a descriptive qualitative research method with data sources obtained through interviews, observation and literature study. The research results show that the implementation of the No-Smoking Area Policy in an effort to fulfill children's rights in the City of Surakarta, through the Peraturan Daerah Kota Surakarta Nomor 9 Tahun 2019 tentang Kawasan Tanpa Rokok, has not been fully optimal. In the Civil Rights and Freedoms Cluster, there are still many Child-Friendly Information Points (ILA) found in Cigarette Advertisements, Promotions and Sponsorships (IPS) which are scattered in areas frequently accessed by children. Then, the Cluster of Basic Health and Welfare Rights is also not aligned with existing policy objectives. This is evidenced by the fact that there are still many portraits of the public and OPD smoking in areas that have been legalized as No-Smoking Areas. So, the advice that can be given is to immediately carry out monitoring and evaluation of regional regulations by the Health Office and DP3AP2KB of Surakarta City and enforcement of sanctions as a deterrent effect for the community and OP who violate regional regulations.